Penerapan Kota Cerdas melalui Citizen Relation Management dalam Pelayanan Publik - Cahyani, Asya Putri; Ode, Samsul; Herawati, Dewi Maria (Jurusan Ilmu Politik Universitas Bangka Belitung, 2020)
Jakarta Province applies smart cities through the Citizens Relations Management program that is used by stakeholders. The program is to hold and to continue at a time when and just as long. The only thing that is done is like CRM Among the reasons for the fall, the length of the road, the road, the infrastructure and then the road infrastructure and the damage to road infrastructure. The method used in this study will only be in the quota of the quota. The method of collecting the two used in this study is the time of the people, as well as and summarized. Only has been that the CRM program has been running well because all the indicators used have included aspects of the implementation of the CRM program. As for some of the past in CRM, which has been used as a result of the CRM.